Ketidaklangsungan Ekspresif dalam Lagu Pretender Karya HIGE DANdism: Kajian Semiotika Riffaterre - Damayanti, Erika Selphie; Mintarsih, Mintarsih (Japanese Department Faculty of Cultural Science Universitas 17 Agustus 1945 Surabaya, 2024)
This study aims to analyze the meaning of the word “pretender” in the song Pretender by HIGE DANdism. This research uses descriptive-qualitative methods with literature techniques, non-interactive, and listening methods. The lyrics in the song entitled Pretender are written in Japanese. Through descriptive analysis techniques, 7 data were found in the Pretender song lyrics. Based on the results and discussion, it can be concluded that expressive indirectness in Riffaterre's semiotic theory can explore the implied meaning in song. These implied meanings are characterized by displacement of meaning in the form of similes, hyperbole and metaphors; The distortion of meaning that appears in this song is in the form of ambiguity; and the creation of meaning in the form of homologue i.e the words motto chigau and sou negattemo. The indirectness of these expressions is used to reinforce the pretense of the character I (Me). Thus, the conclusion of this research is that the meaning of pretending in the Pretender song by HIGE DANdism is in accordance with the literal meaning, which is to show or express something that is inversely proportional to what is felt. So, hiding the true feelings. Keywords: Riffaterre semiotics, pretender, HIGE DANdism, expressive indirectness, song